Analysis of Quality Development of Kaopi Products Using The Quality Function Deploment (QFD) Method (Case Study on Raysa Smes In Eelahaji Village, Kulisusu District, North Buton Regency) - Resen Yusmitha Mustahara; Sarinah Sarinah; Weka Gusmiarty Abdullah (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to: (a) know the process of making kai products; and (b) know the process of developing the quality of Raysa Small Enterprises' kaopi products in Eelahaji Village, Kulisusu District, North Buton Regency using the Quality Function Deployment (QFD) method. Data collection was carried out using interviews, observation and literature review. The results showed that the prioritized attributes in the development of Raysa's Small Business coffee products were by the wishes and needs of consumers, respectively, namely price compatibility with product quality (12.1%), availability every day (12.1%), fast service (11.3%), the texture is not hard and has fibre (11.1%), discounted prices for purchasing multiple products (10.9%), easy access to products (10.9%), affordable prices Rp. 7000/2kg (10.8%), product shelf life can last ≥ 3 days (10.4%) and has the aroma of cassava (10.3%). There are 9 attributes of consumer desires and 7 technical responses that are a priority in the process of developing the quality of UKM Raysa's kaopi products in the form of selecting raw materials, supplying raw materials, the washing process, grating process, printing process, pressing process and creating a marketing system.